2011
DOI: 10.1186/1749-8090-6-161
|View full text |Cite
|
Sign up to set email alerts
|

A long-term study assessing the factors influencing survival and morbidity in the surgical management of bronchiectasis

Abstract: BackgroundAlthough the prevalence of bronchiectasis decreased significantly in developed countries, in less developed and in developing countries, it still represents a significant cause of morbidity and mortality. The aim of this retrospective study is to present our surgical experiences, the morbidity and mortality rates and outcome of surgical treatment for bronchiectasis.MethodsWe reviewed the medical records of 129 patients who underwent surgical resection for bronchiectasis between April 2002 and April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
(26 reference statements)
1
12
0
2
Order By: Relevance
“…Besides medical treatment and respiratory physiotherapy, surgical treatment is an eligible therapy for patients with non-CF bronchiectasis, especially to those with little response to conservative interventions 7 . Over the years, many studies have reported surgical intervention in the management of patients with non-CF bronchiectasis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . The surgical procedure was aimed at primary resection of the affected area, as assessed by high-resolution computed tomographic (HRCT).…”
mentioning
confidence: 99%
“…Besides medical treatment and respiratory physiotherapy, surgical treatment is an eligible therapy for patients with non-CF bronchiectasis, especially to those with little response to conservative interventions 7 . Over the years, many studies have reported surgical intervention in the management of patients with non-CF bronchiectasis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 . The surgical procedure was aimed at primary resection of the affected area, as assessed by high-resolution computed tomographic (HRCT).…”
mentioning
confidence: 99%
“…To note, 2 major complications, empyema and persistent air leak, occurred but A, Data from the present study; B, data from the study by Zhang and colleagues 4 ; C, data from the study by Gursoy and colleagues 15 ; and D, data from the study by Sehitogullari and colleagues. 16 both were manageable without the need for reoperation. Postoperative empyema was common in bronchiectasis, 6,16 and most could be treated successfully by tube thoracostomy.…”
Section: Discussionmentioning
confidence: 86%
“…16 both were manageable without the need for reoperation. Postoperative empyema was common in bronchiectasis, 6,16 and most could be treated successfully by tube thoracostomy. In addition, persistent air leak was frequently noted after operation, with a reported rate of 4.8% to 6.1%.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations